Fire risk assessment of heritage building: the influence of regulatory body and restorer’s background on the assessment criteria - Ibrahim, Md. Najib; Ibrahim, Mohd Shariffuddin; Mohd Din, Azrin; Ali, Maisarah; Mohd Yunus , Rodzyah; Yahya , Mohamad Ridzuan (Ministry of Higher Education, 2013)
The assessment of fire risk of heritage buildings is subjective which depend on the background of stakeholders. The relative significance of every factor and its particular attributes of the risk depend on the background of the assessor. This research established a new method so that the assessment will be more objective. A survey questionnaire was developed based on the identified criteria and attributes of fire risks for heritage buildings. The survey questionnaire was applied as interview checklist for structured interview. Expert panels of heritage building between Fire Rescue Department (FRDM) personnel and restoration practitioners were interviewed. The data were analysed using the Analytical Hierarchy Method (AHP). The result of the research is the weightage for each criterion and its respective attributes. When the common weightages is applied the assessment of all assessors will be more objective.